Determination and Analysis of Trends in Mechanical Loads Acting on Stair Handrails During Climbing - NARITA, Runa; MORIOKA, Daisuke (Advanced Experimental Mechanics, 2025)
Previous studies on the biomechanics of handrail use have primarily involved evaluation methods using sensors worn on the body (e.g., joint moments) and qualitative evaluations. If the load and grip strength acting on a handrail can be measured, then direct measurement would be possible without reliance on worn sensors or qualitative evaluations. In this study, we report the development of a system for measuring the mechanical loads on handrails and its use to clarify the trends in such loads during stair climbing. Mechanical loads on the handrail are measured using a 3-axis force sensor and two strain gauges. Subjects in the experiment were right-handed 10 healthy adults. The results showed that the grip duration on the handrail could vary by up to a factor of 2.6 depending on the subject. Also, the direction of the force acting on the handrail helped to elucidate the role of stair handrails. Future research will focus on moments around each axis to identify load application points, thereby further clarifying the role of stair handrails.